2015
DOI: 10.1249/mss.0000000000000455
|View full text |Cite
|
Sign up to set email alerts
|

Caffeinated Energy Drinks Improve Volleyball Performance in Elite Female Players

Abstract: Commercially available energy drinks can significantly improve physical performance in female volleyball players. Increased physical performance led to improved accuracy during an actual volleyball match.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
95
4
11

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 92 publications
(122 citation statements)
references
References 36 publications
(38 reference statements)
12
95
4
11
Order By: Relevance
“…A number of recent investigations have concluded that caffeine enhances exercise performance in populations of female athletes . In addition, a recent investigation indicates that caffeine might have a similar ergogenic effect in men and women, at least during an endurance performance trial in cycling .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of recent investigations have concluded that caffeine enhances exercise performance in populations of female athletes . In addition, a recent investigation indicates that caffeine might have a similar ergogenic effect in men and women, at least during an endurance performance trial in cycling .…”
Section: Discussionmentioning
confidence: 99%
“…16 A number of recent investigations have concluded that caffeine enhances exercise performance in populations of female athletes. [30][31][32][33] In addition, a recent investigation indicates that caffeine might have a similar ergogenic effect in men and women, at least during an endurance performance trial in cycling. 34 However, these findings contrast with the lack of effect of caffeine to increase peak and mean cycling performance on the Wingate test in women, 11 while it seems that caffeine effectiveness to increase anaerobic performance might be lower in women than in men despite the use of the same dose of caffeine.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, our data have shown that a dose of 3 mg·kg −1 of caffeine improved both peak and mean power during the test. Likewise, recent research has demonstrated an ergogenic effect in power activities, both in lower and upper limb exercises, such as power in half squats or bench presses, jumps, or repeated jumps in 15 s [2,5,8]. This ergogenic effect in anaerobic performance could be due to the influence of caffeine on the Na+/K+ pump, facilitating Na+/K+ATPase activity [19].…”
Section: Discussionmentioning
confidence: 99%
“…The scientific evidence regarding the performance-enhancing properties of caffeine has been found in short-term high-intensity sports modalities [2], team sports competitions [3,4,5], and endurance-based exercise [6,7]. Moreover, the pre-exercise ingestion of caffeine is effective in increasing physical performance in resistance activities [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…(42) The results of a recent study reported that consumption of approximately 3 mg/kg of caffeine in the form of energy drinks significantly improved the physical performance of female volleyball players. (43) Wesnes et al in a randomized, double blind, placebo controlled, cross over study examined the cognitive and mood effects of energy drinks on 94 subjects. Assessment of cognitive function was performed with a number of automated tests of memory and attention while mood was assessed with various different questionnaires such as the Profile of Mood states (POMS), Bond-Lader and Chalder Fatigue Scales.…”
Section: Renal Effectsmentioning
confidence: 99%